1994
DOI: 10.1590/s0034-89101994000100004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência da síndrome cerebral orgânica em população de idosos de área metropolitana da região sudeste do Brasil

Abstract: Foram apresentados os principais resultados do estudo de prevalência de síndrome cerebral orgânica, realizado na cidade do Rio de Janeiro, com a população idosa. A partir de um conjunto de indicadores foram selecionados três distritos: Copacabana, Méier e Santa Cruz. No de Copacabana foi realizado o estudo de validação e confiabilidade do instrumento de diagnóstico. Os resultados de prevalência em Copacabana, Méier e Santa Cruz para síndrome cerebral orgânica foram de 5,9%, 9,8% e 29,7%, respectivamente. Vária… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
3
0
4
Order By: Relevance
“…In European countries and the USA, 10 to 15% of individuals over 65 years old present some cognitive deficit and 5% present dementia 1,24 . In a study carried out in Rio de Janeiro, Brazil concerning the prevalence of organic brain syndrome the results varied from 5.9 to 29.7% in three different districts 42 . Almeida Filho 2 showed, in the state of Bahia, 6.8% of cases of dementia and 36.4% of some mental disorder syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…In European countries and the USA, 10 to 15% of individuals over 65 years old present some cognitive deficit and 5% present dementia 1,24 . In a study carried out in Rio de Janeiro, Brazil concerning the prevalence of organic brain syndrome the results varied from 5.9 to 29.7% in three different districts 42 . Almeida Filho 2 showed, in the state of Bahia, 6.8% of cases of dementia and 36.4% of some mental disorder syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…In Latin America, very few studies have reported the frequency of dementia, finding a wide range from 0.40% in Uruguay to 29.7% in a district of Rio de Janeiro, Brazil [3][4][5]. Considering the highly heterogeneous origins and living conditions in Latin America, as well as the difficulties of establishing a diagnosis of dementia in population-based studies, particularly in the early stages of the pathology among subjects with low levels of education, these results are not unexpected.…”
Section: Introductionmentioning
confidence: 99%
“…As prevalências de Santa Cruz mostraram-se atípicas, principalmente se levarmos em consideração que a mesma metodologia, o instrumento e os entrevistadores foram utilizados nas áreas estudadas. O fato de Santa Cruz apresentar uma associação bastante forte com SCO, mesmo depois de ajustar os dados por idade, renda e escolaridade, precisa ser mais bem explorado, e a hipótese ligada ao problema do instrumento foi objeto de um artigo recente (Veras & Coutinho, 1994). Assim, é possível que o instrumento de pesquisa utilizado para estabelecer o diagnóstico de SCO não seja adequado ao uso em determinados segmentos socioeconômicos, podendo apresentar resultados enganosos.…”
Section: Discussão Dos Resultados Do Estudo Comunitáriounclassified